2023
DOI: 10.3390/math11040860
|View full text |Cite
|
Sign up to set email alerts
|

How Tourists’ Perceived Risk Affects Behavioral Intention through Crisis Communication in the Post-COVID-19 Era

Abstract: In the post-COVID-19 era, with tourism activity beginning to revitalize, the behavioral intention of tourists has emerged as the focus of much research interest. While previous studies have suggested that tourists’ perceived risk affects behavioral intention, it has not been found that perceived risk is influenced by other factors that affect behavioral intention in the post-COVID-19 era. This study constructs a research model to understand how tourists’ perceived risk influences emotional attachment to destin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…This means that the more Z-generation users perceive psychological recovery, the deeper their attachment to the online digital exhibition venue, which, in turn, influences their loyalty. Chen et al (2023) suggested that people during and after the COVID-19 pandemic may develop a stronger attachment to places that offer healing and recovery. In future website design for online digital art exhibitions, curators and designers can leverage the relationship between website aesthetics, perceived recovery, and place attachment to create a comfortable online exhibition environment for Z-generation young individuals, thereby enhancing their happiness.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This means that the more Z-generation users perceive psychological recovery, the deeper their attachment to the online digital exhibition venue, which, in turn, influences their loyalty. Chen et al (2023) suggested that people during and after the COVID-19 pandemic may develop a stronger attachment to places that offer healing and recovery. In future website design for online digital art exhibitions, curators and designers can leverage the relationship between website aesthetics, perceived recovery, and place attachment to create a comfortable online exhibition environment for Z-generation young individuals, thereby enhancing their happiness.…”
Section: Conclusion and Discussionmentioning
confidence: 99%